Experimental Study of Operating Conditions and Integration of Thermoelectric Materials in Facade Systems - Aksamija, Ajla; Aksamija, Zlatan; Counihan, Chris; Brown, Dylan; Upadhyaya, Meenakshi (Frontiers in Energy Research, 2019)
This article discusses the application of thermoelectric (TE) materials in building facade systems, which can be used to create active exterior enclosures. TEs are semiconductors that have the ability to produce a temperature gradient when electricity is applied, exploiting the Peltier effect, or to generate a voltage when exposed to a temperature gradient, utilizing the Seebeck effect. TEs can be used for heating, cooling, or electricity generation. In this research, heating and cooling applications of these novel systems were explored. We designed and constructed two prototypes, where one prototype was used to study integration of TE modules (TEMs) as stand-alone elements in the facade, and one prototype was used to explore integration of TEMs and heat sinks in facade assemblies. Both prototypes were tested for heating and cooling potential, using a thermal chamber to represent four different exterior environmental conditions (-18°C, -1°C, 16°C and 32°C). The interior ambient conditions were kept constant at room temperature. The supplied voltage to facade-integrated TEMs varied from 1 to 8 V. We measured temperature outputs of TEMs for all investigated thermal conditions using thermal imaging, which are discussed in this article. The results indicate that while stand-alone facade-integrated TEMs are not stable, addition of heat sinks improves their performance drastically. Facade-integrated TEMs with heatsinks showed that they would operate well in heating and cooling modes under varying exterior environmental conditions.